2022
DOI: 10.1536/ihj.21-627
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Immune-Inflammation Index Predicts Embolic Events in Infective Endocarditis

Abstract: Infective endocarditis (IE) is a life-threatening disease with embolisms occurring in 20%-50% of cases. We aimed to evaluate the value of the systemic immune-inflammation index (SII) in predicting embolic events (EEs) in patients with infective endocarditis.A total of 186 patients diagnosed with definite IE, who admitted to the Union Hospital affiliated to Tongji Medical College, Huazhong University of Science and Technology, were retrospectively identified from November 2011 to March 2019.The median (interqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…24 Having higher SII was associated with embolic events in these patients. 31 In the present study, patients with CIED infection had higher SII values before the procedure compared with those without CIED infection. Higher SII before the procedure may be a sign of infection or inflammation, especially in cases having early infection risk.…”
Section: Discussionsupporting
confidence: 48%
“…24 Having higher SII was associated with embolic events in these patients. 31 In the present study, patients with CIED infection had higher SII values before the procedure compared with those without CIED infection. Higher SII before the procedure may be a sign of infection or inflammation, especially in cases having early infection risk.…”
Section: Discussionsupporting
confidence: 48%
“… 5 Recently two studies have found that high SII levels are independently associated with mortality and embolic events in IE. 6 , 7 NLR has been shown to have a high predictive value for many cardiovascular diseases. However, data are scarce on its predictive value in IE patients.…”
Section: Introductionmentioning
confidence: 99%